BELA NEGARA DALAM PERSPEKTIF AL-QUR’AN (Sebuah Transformasi Makna Jihad) - Mustaqim, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2011)
Transnational ideology springs the faded attitude of state defend. In another side, state defend is always connected with military. The concept of jiha>d (struggle) in the Qur’an can be understood as an obligation to defend the state in all levels. The obligation could be in the form of guarding unity and integrity, culturalizing of deliberation, struggling justice and maintaining freedom. The obligation of state defend in the form of physical form could not be conducted whether individually or collectively. This obligation is performed only if a ruler commands to battle against, and when an enemy has besieged a region. If defending Indonesia state is one of requirements for existence and glory of muslims in materializing Islamic values and universal of humanity, so struggling for state defend is a condition sine qua non